Pengembangan Bahan Ajar Matematika Materi Turunan dengan Model Discovery Learning - Salmun, Ahmad (Media Nusantara, 2021)
This research’s background is the low of senior high school student’s mathematical communication ability. Thus, researcher gives the solution to develop the teaching material to improve senior high school student’s mathematical communication ability. The research method is research and development design comprising Dick & Carey model. This research involves class XI MIA 2 students in one of Senior High School in Bandung. The data’s collected by document analysis, survey, questionnaire, and test. The instruments are validation sheet, mathematical communication test, observation sheet, student’s journal, and questionnaire. Based on data processing and analyzing about teaching material development show that teaching material characteristic appropriates with content standard of Curriculum 2013 and the material presentation appropriates with discovery learning model; and teaching material design consist of preface section (title page, foreword, table of contents, and using directions) and content section (performance competence, sub material titles, example and illustration of daily activity problem, material, supporting information and mathematic figures, example with the solution, exercise, resume, and evaluation). Meanwhile, the result of data processing and analyzing, generally respondents give the positive response to mathematical teaching material on derivative using discovery learning.